FACTORS RELATED TO THE SUCCESSFUL TREATMENT OF TUBERCULOSIS: A LITERATURE REVIEW - Kusuma Wijaya Ridi Putra; Chanandchidadussadee Toonsiri (Belitung Nursing Journal, 2019)
Background: Many tuberculosis sufferers experience recurrent events due to incomplete treatment processes. It is often found that tuberculosis sufferers re-enter the hospital because the condition is getting worse. Thus, factors related to the successfulness of the treatment of tuberculosis warrant identification. Objectives: This review was to summarize and identify the current literature related to the successful treatment of tuberculosis and its factors. Design: A Whittemore and Knafl’s integrative review was used. Data Sources: Data sources included four electronic databases: EBSCO, PubMed, Science Direct and Google Scholar to search literature published between 2002 and 2017. Review methods: A systematic process was carried out to extract and analyze the data of all included studies. Results: A total of 146 articles were deemed appropriate for the topic, but only 28 articles were included based on inclusion criteria. It was found that a wide range of factors related to the successful treatment of tuberculosis, including predisposing factors (socioeconomic, knowledge, psychological stress, and availability to access health service), reinforcing factor (family support and social stigma), and enabling factor (physician and nurse support). Conclusion: Family support, socioeconomic, physician and nurse support, availability to access health services, social stigma, psychological stress, and knowledge were significant factors of the successful treatment of tuberculosis. For future research, the interventions to promote the program for decreasing the occurrence of the recurrent tuberculosis in the community need to consider these factors for the successful treatment of tuberculosis and collaborates with tuberculosis patients, family and health service for development of appropriate intervention.